Purines as Transmitter Molecules: Electrophysiological Studies on Purinergic Signalling in Different Cell Systems - Elisabetta Coppi (Firenze University Press, 2008)
Purinergic nucleotides and nucleosides (ATP, ADP, AMP and adenosine) are essential intracellular metabolites involved in a number of cellular processes, from energy supply to protein phosphorylation. However, in the last years, several studies demonstrated their involvement in cell signalling by the activation of specific membrane receptors (P1 and P2) and their role as neurotransmitters began to be investigated. The present work was aimed to clarify the effects of purinergic neurotransmission in different cell systems by using electrophysiological techniques. Relevant results of this research include the observation that P1 and P2 receptors play a deleterious role during "in vitro" ischemia in the rat brain, and the first demonstration of P2 receptor expression and function in a line of adult human mesenchymal stem cells.
Keywords: Metabolismo; Open Access; Acidi nucleici; Chimica; Chimica inorganica; Fisiologia